The working of parliamentary committees in Westminster systems : lessons for Bangladesh - Ahmed, Nizam; Obaidullah, A. T. M. (University Press, 2007)
Proceedings of the International Workshop on Parliamentary Committees in Westminster Systems : Lessons for Bangladesh, held at Dhaka on 31st July 2005.